Implications of digital transformation and digital resilience: An empirical study of the social media adoption of selected online food MSMEs during the COVID-19 pandemic in Metro Manila, Philippines - Alcira, Maika Elise M. (Animo Repository, 2022)
Ever since the Coronavirus pandemic, businesses in the Philippines had to innovate and adapt to the changes by digitizing their products and services. Thus, this study aimed to analyze the moderating effect of social media adoption on the relationship between digital transformation and digital resilience based on online food MSMEs, specifically BOA Asian Flavors, Chef Baby’s and Chicken Basket restaurant. Digital transformation is how digital technologies are incorporated within business operations. Digital resilience allows businesses to understand and manage the risks and challenges they continue to face in order to recover quickly from possible threats and its effects. Social media adoption is the inclusion of social media platforms to promote online businesses. BOA Asian Flavors digitally transformed well and displayed digital resilience as they responded quickly when they were seeing bad results, guided and trained employees on how to handle specific tasks, managed social media accounts well and allowed employees to voice out their concerns. Chef Baby’s had a plan before transitioning digitally, smooth execution of digital business strategy, but lacked employee training lowering their resilience. Lastly, Chicken Basket was guided by a well-experienced marketing head, managed social media accounts well, trained employees on how to handle specific tasks, made use of digital advertising and allowed their employees to brainstorm and share their ideas. This leads to them being digitally resilient. The researchers recommend these companies to learn from one another and apply the practices that work best for each such as exhibiting proper training and maintaining good communication channels between employees and managers.